Uncovering Social Media Preference of Non-EFL/ESL Students in English Learning at Higher Education - Yani, Muhammad; Palanee, Matthuri; Subramaniam, Barathimani; Wathoni, Nur Ilmi; Aiza, Izatul (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
Social media, an Internet-based technology, enables students to receive and share information, leading to an upsurge in English learning. Facebook, Instagram, TikTok, and YouTube are some of the most popular social networking apps for students. Thus, the present research was conducted to expose non-EFL/ESL university students' preferences in learning English. A mixed-method research design was used to process the research, and an open-ended questionnaire (Quanti) and semi-structured interview (Quali) were employed. Using purposive sampling, 77 students participated voluntarily, and the data were analyzed using descriptive statistics and thematic analysis. The finding revealed that YouTube was the most preferred among other platforms, TikTok was the second most favourable, followed by Instagram, and Facebook was the least. The preferences were determined according to the enjoyment, system quality, information quality, interactivity, perceived usefulness and satisfaction with the applications. The present research is beneficial as evidence for an upcoming study comparing the effectiveness of these social media platforms for future English education, especially the features and exploring the users' belief in utilizing the devices.